White carbon black wet rubber, preparation method thereof and vulcanized rubber
By mixing white carbon black, phospholipid emulsion and coagulase, the problem of high energy consumption and poor dispersion of traditional dry processes is solved, and efficient and environmentally friendly white carbon black wet glue preparation is achieved, and the mechanical properties of vulcanized glue are improved.
Patent Information
- Application Number
- CN202411975528.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The traditional white carbon black dry mixing process has problems such as high energy consumption, high dust pollution and poor dispersion of white carbon black, which affects the performance of the glue. The existing white carbon black wet glue requires pre-emulsified natural rubber latex, and the white carbon black is unevenly dispersed, which affects the mechanical properties of the vulcanized glue.
The white carbon black emulsion is prepared by mixing white carbon black, phospholipid emulsion and coagulase, and mixed with natural rubber latex. After standing and solidifying and drying, the white carbon black wet glue is obtained. This method omits the pre-emulsification step of natural rubber latex, improves production efficiency, and improves the dispersion of white carbon black and the mechanical properties of vulcanized rubber by using phospholipids as dispersants and coagulase as coagulants.
The efficient preparation of white carbon black wet glue is achieved, and the mechanical properties of vulcanized glue are improved, including tensile strength, fixed extension stress and white carbon black dispersion, and the production cost is reduced.
Smart Images

Figure BDA0005220353890000061 
Figure BDA0005220353890000071 
Figure BDA0005220353890000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of natural rubber and rubber products, and specifically relates to a white carbon black wet-process rubber and a preparation method thereof, and a vulcanized rubber. Background Art
[0002] In the rubber industry, white carbon black is a common reinforcing agent, and its reinforcing effect exceeds that of any other white reinforcing agent, which can give the rubber compound higher tensile strength, tensile stress, tear strength and heat resistance. The traditional white carbon black dry mixing process mainly puts the pre-treated white carbon black into the mixing equipment, mixes it with the rubber component under the action of mechanical shear force and stirring force, and mixes it evenly by controlling the mixing temperature, time, speed and other process parameters. This process is a high-energy consumption and high-dust pollution process, and the dispersibility of white carbon black is greatly limited by the process parameters, which affects the performance of the rubber compound.
[0003] Compared with the traditional dry mixing process, wet mixing has significant advantages in environmental protection, energy consumption, dispersion effect, production efficiency and quality stability. However, the existing wet-mix silica rubber requires pre-emulsification of natural rubber latex, and the silica still has the disadvantage of uneven dispersion, which affects the mechanical properties of the final vulcanized rubber. Summary of the invention
[0004] The purpose of the present invention is to provide a white carbon black wet-process rubber and a preparation method thereof, as well as a vulcanized rubber. The preparation method provided by the present invention omits the pre-emulsification step of natural rubber latex, thereby improving production efficiency; at the same time, the obtained vulcanized rubber has excellent mechanical properties and has industrial application value.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a white carbon black wet-process rubber, comprising the following steps:
[0007] mixing white carbon black, phospholipid emulsion and coagulase to obtain white carbon black emulsion;
[0008] Mixing the white carbon black emulsion and natural rubber latex to obtain a paste;
[0009] The paste is sequentially placed to solidify and dried to obtain the white carbon black wet-process glue.
[0010] Preferably, the white carbon black includes one or more of fumed white carbon black, hydrophilic white carbon black and lipophilic white carbon black.
[0011] Preferably, the method for preparing the oleophilic white carbon black comprises the following steps:
[0012] A silane coupling agent is used to hydrophobically modify fumed silica to obtain lipophilic silica; the mass percentage of the silane coupling agent in the fumed silica is 10-20%.
[0013] Preferably, the phospholipid emulsion comprises phospholipids and water, and the phospholipids comprise one or more of phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine.
[0014] Preferably, the mass percentage of phospholipids in the phospholipid emulsion to the white carbon black is 1-5%.
[0015] Preferably, the mass ratio of the white carbon black to the dry rubber in the natural rubber latex is 1:2-3.
[0016] Preferably, the coagulase is a protease; the mass percentage of the coagulase in the dry rubber in the natural rubber latex is 0.1-1%.
[0017] Preferably, the standing solidification time is 8 to 24 hours; and the drying temperature is 100 to 120°C.
[0018] The present invention provides white carbon black wet-process rubber prepared by the preparation method described in the above technical scheme.
[0019] The present invention provides a vulcanized rubber, comprising the following raw materials in parts by weight:
[0020] The above technical solution comprises 150-180 parts of white carbon black wet-process rubber, 3-5 parts of zinc oxide, 1-2 parts of stearic acid, 1-2 parts of antioxidant, 2-6 parts of coupling agent, 2-3 parts of accelerator and 1-2 parts of sulfur.
[0021] The present invention provides a method for preparing a white carbon black wet process rubber, comprising the following steps: mixing white carbon black, a phospholipid emulsion and a coagulase to obtain a white carbon black emulsion; mixing the white carbon black emulsion and natural rubber latex to obtain a paste; and sequentially performing static coagulation and drying on the paste to obtain the white carbon black wet process rubber. The present invention uses an amphiphilic phospholipid in the phospholipid emulsion as a dispersant for white carbon black, which can effectively improve the dispersion of white carbon black in natural rubber, thereby improving the mechanical properties of the vulcanized rubber. At the same time, the phospholipid in the phospholipid emulsion can also be used as a plasticizer to improve the processing performance (including processing operations such as mixing and calendering) of the obtained white carbon black wet process rubber. In addition, the present invention introduces a coagulase with a long coagulation time as a coagulant, thereby ensuring that white carbon black has sufficient dispersion time in natural rubber latex, and under the dispersing effect of phospholipids, it can ensure that white carbon black is evenly dispersed in natural rubber latex. After the rubber is coagulated, the white carbon black can be fully wrapped in the rubber molecules, which can not only improve the mechanical properties of the vulcanized rubber obtained by using white carbon black wet rubber as raw rubber, but also effectively reduce the processing loss rate of white carbon black. In summary, the preparation method provided by the present invention uses phospholipids as a dispersant and auxiliary coagulase as a coagulant, thereby improving the mechanical properties of the vulcanized rubber, and at the same time, there is no need to pre-emulsify the natural rubber latex, thereby improving the production efficiency of white carbon black wet rubber and reducing the cost. The results of the embodiments show that the vulcanized rubber prepared by using the white carbon black wet process rubber provided by the present invention has excellent comprehensive properties. The tensile strength of the vulcanized rubber is tested to be 28-32 MPa, the 300% elongation stress is 18-21 MPa, the ash content is 29-33%, the white carbon black dispersion is 8-9, and the heat generation is 26-29°C. DETAILED DESCRIPTION
[0022] The present invention provides a method for preparing a white carbon black wet-process rubber, comprising the following steps:
[0023] mixing white carbon black, phospholipid emulsion and coagulase to obtain white carbon black emulsion;
[0024] Mixing the white carbon black emulsion and natural rubber latex to obtain a paste;
[0025] The paste is sequentially placed to solidify and dried to obtain the white carbon black wet-process glue.
[0026] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0027] The present invention mixes white carbon black, phospholipid emulsion and coagulase to obtain white carbon black emulsion. In the present invention, the white carbon black preferably includes one or more of fumed white carbon black, hydrophilic white carbon black and lipophilic white carbon black. The hydrophilic white carbon black is preferably REOLOSIL QS-102 type hydrophilic white carbon black, purchased from Tokuyama Company. The preparation method of the lipophilic white carbon black preferably includes the following steps: hydrophobically modifying the fumed white carbon black with a silane coupling agent to obtain lipophilic white carbon black. The silane coupling agent is preferably KH-560. The mass percentage of the silane coupling agent to the fumed white carbon black is preferably 10 to 20%, more preferably 10%. The hydrophobic modification preferably includes the following steps: dispersing the fumed white carbon black in a silane coupling agent solution to perform the hydrophobic modification. The silane coupling agent solution preferably includes a silane coupling agent, ethanol and water, and the mass percentage of the silane coupling agent in the silane coupling agent solution is preferably 5-15%, more preferably 10%. The mass ratio of ethanol to water is preferably 8-9:1, more preferably 8:1. The temperature of the hydrophobic modification is preferably 50-60°C, and the time is preferably 6-8h. After the hydrophobic modification is completed, a modified liquid is obtained. The present invention preferably performs solid-liquid separation, washing and drying on the modified liquid in sequence to obtain the lipophilic white carbon black. The washing is preferably performed by alternating washing with water and ethanol. The drying temperature is preferably 45-50°C.
[0028] In the present invention, the phospholipid emulsion includes phospholipids and water, and the phospholipids preferably include one or more of lecithin, phosphatidylethanolamine and phosphatidylserine, and more preferably lecithin. The present invention has no special requirements for the amount of water in the phospholipid emulsion. The mass percentage of phospholipids in the phospholipid emulsion to the white carbon black is preferably 1-5%, and can be 2% or 4% in the embodiment. The present invention uses phospholipids (preferably lecithin) as a dispersant for white carbon black and as a plasticizer for natural rubber. Compared with the use of surfactants (such as sodium dodecyl sulfate or Triton), the present invention uses phospholipids as a dispersant for white carbon black, which will not have an adverse effect on the coagulation of natural rubber latex; at the same time, the present invention can obtain vulcanized rubber with excellent mechanical properties by controlling the mass ratio of phospholipids and white carbon black.
[0029] In the present invention, the coagulase is preferably a protease, more preferably papain and / or bromelain. The mass percentage of the coagulase in the dry rubber in the natural rubber latex is preferably 0.1-1%, and can be 0.1% in the embodiment. The present invention can make the natural rubber latex have a suitable coagulation time by controlling the mass ratio of the coagulase to the dry rubber in the natural rubber latex, thereby ensuring that the white carbon black is fully dispersed in the natural rubber latex, and the latex is fully wrapped in the rubber molecules after coagulation, so as to obtain a white carbon black wet process rubber with excellent performance.
[0030] The present invention has no special requirements on the specific implementation method of mixing the white carbon black, phospholipid emulsion and coagulase, and they can be evenly mixed by stirring.
[0031] After obtaining the white carbon black emulsion, the present invention mixes the white carbon black emulsion and natural rubber latex to obtain a paste. In the present invention, the mass ratio of the white carbon black to the dry rubber in the natural rubber latex is 1:2-3, and can be 1:2 in the embodiment. The present invention has no special requirements for the specific implementation of mixing the white carbon black emulsion and natural rubber latex, and stirring and mixing uniformly until a viscous paste is obtained.
[0032] After obtaining the paste, the present invention sequentially performs static solidification and drying on the paste to obtain the white carbon black wet process glue. In the present invention, the static solidification is performed in a stainless steel tray, the static solidification temperature is room temperature, and the static solidification time is preferably 8 to 24 hours. In the embodiment, it can be 12 hours. The drying temperature is preferably 100 to 120°C.
[0033] The present invention provides white carbon black wet-process rubber prepared by the preparation method described in the above technical scheme.
[0034] The present invention provides a vulcanized rubber, comprising the following raw materials in parts by weight:
[0035] The above technical solution comprises 150-180 parts of white carbon black wet-process rubber, 3-5 parts of zinc oxide, 1-2 parts of stearic acid, 1-2 parts of antioxidant, 2-6 parts of coupling agent, 2-3 parts of accelerator and 1-2 parts of sulfur.
[0036] In terms of parts by mass, the raw materials for preparing the vulcanized rubber provided by the present invention include 150 to 180 parts of the white carbon black wet-process rubber described in the above technical solution, and in the embodiment, it can be 150 parts.
[0037] Based on the preparation quantity of the white carbon black wet process rubber, the raw materials for preparing the vulcanized rubber provided by the present invention include 3 to 5 parts of zinc oxide, and in the embodiment, it can be 5 parts.
[0038] Based on the preparation quantity of the white carbon black wet rubber, the raw materials for preparing the vulcanized rubber provided by the present invention include 1 to 2 parts of stearic acid, and in the embodiment, it can be 1.5 parts.
[0039] Based on the number of prepared white carbon black wet rubber, the raw materials for preparing the vulcanized rubber provided by the present invention include 1 to 2 parts of antioxidant, and in the embodiment, it can be 1.5 parts. In the present invention, the antioxidant is preferably antioxidant 4010NA.
[0040] Based on the number of prepared white carbon black wet rubber, the raw materials for preparing the vulcanized rubber provided by the present invention include 2 to 6 parts of coupling agent, and in the embodiment, it can be 5 parts. In the present invention, the coupling agent is preferably coupling agent KH-845-4.
[0041] Based on the number of prepared white carbon black wet rubber, the raw materials for preparing the vulcanized rubber provided by the present invention include 2 to 3 parts of accelerator, and in the embodiment, it can be 3 parts. In the present invention, the accelerator preferably includes accelerator CZ and accelerator D, and the mass ratio of the accelerator CZ to the accelerator D is preferably 2:1.
[0042] Based on the preparation quantity of the white carbon black wet process rubber, the raw materials for preparing the vulcanized rubber provided by the present invention include 1 to 2 parts of sulfur, and in the embodiment, it can be 1.5 parts.
[0043] The vulcanized rubber provided by the present invention uses the white carbon black wet-process rubber described in the above technical solution as raw rubber to prepare a mixed rubber, and the obtained vulcanized rubber has excellent mechanical properties.
[0044] The vulcanized rubber provided by the invention has a tensile strength of 28-32 MPa, a 300% elongation stress of 18-21 MPa, an ash content of 29-33%, a white carbon black dispersion of 8-9, and a heat generation of 26-29°C.
[0045] In the present invention, the method for preparing the vulcanized rubber preferably comprises the following steps:
[0046] Mixing white carbon black wet rubber, coupling agent, zinc oxide, stearic acid, antioxidant, sulfur and accelerator to obtain mixed rubber;
[0047] The mixed rubber is vulcanized to obtain the vulcanized rubber.
[0048] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0049] Example 1
[0050] 100g of silane coupling agent KH-560 was prepared into KH-560 solution, and the KH-560 solution was prepared according to the mass content of 10% silane coupling agent KH-560, 80% ethanol and 10% water. 550g of fumed silica (Shandong Aochuang Chemical Co., Ltd.) was dispersed in the KH-560 solution, stirred and reacted at 60°C for 8h, filtered and washed alternately with water and ethanol, and finally dried at 50°C to obtain lipophilic silica.
[0051] 10 g of lecithin was dispersed in water with high-speed stirring to obtain a lecithin emulsion, 500 g of lipophilic white carbon black was added to the lecithin emulsion, and 1 g of coagulase (papain) was added and stirred sufficiently to obtain a lipophilic white carbon black emulsion.
[0052] The lipophilic silica emulsion was blended with natural rubber latex containing 1000 g of dry glue, fully stirred until a viscous paste, transferred to a stainless steel tray and allowed to stand for 12 hours, and dried at 120° C. to obtain a silica wet glue.
[0053] Example 2
[0054] 10 g of lecithin was dispersed in water with high-speed stirring to obtain a lecithin emulsion, 500 g of hydrophilic silica (hydrophilic silica was REOLOSIL QS-102, purchased from Tokuyama Co., Ltd.) was added to the lecithin emulsion, and 1 g of coagulase (papain) was added and stirred thoroughly to obtain a hydrophilic silica emulsion.
[0055] The hydrophilic silica emulsion was blended with natural rubber latex containing 1000 g of dry glue, fully stirred until a viscous paste, transferred to a stainless steel tray and allowed to stand for 12 hours, and dried at 120° C. to obtain a silica wet glue.
[0056] Example 3
[0057] 20 g of lecithin was dispersed in water with high-speed stirring to obtain a lecithin emulsion, 500 g of hydrophilic silica (hydrophilic silica was REOLOSIL QS-102, purchased from Tokuyama Co., Ltd.) was added to the lecithin emulsion and 1 g of coagulase (papain) was added and stirred thoroughly to obtain a hydrophilic silica emulsion.
[0058] The hydrophilic silica emulsion was blended with natural rubber latex containing 1000 g of dry glue, fully stirred until a viscous paste, transferred to a stainless steel tray and allowed to stand for 12 hours, and dried at 120° C. to obtain a silica wet glue.
[0059] Comparative Example 1
[0060] 1 g of coagulase (papain) was mixed with natural rubber latex containing 1000 g of dry rubber, coagulated for 12 h, and dried at 120° C. to obtain natural rubber.
[0061] Comparative Example 2
[0062] The commercially available white carbon black wet-process rubber SF175-50 (manufacturer: Mengla County Manzhuang Rubber Co., Ltd.) was used for comparison.
[0063] Test Case
[0064] Vulcanized rubber was prepared using the white carbon black wet process rubber prepared in Examples 1 to 3, the natural rubber prepared in Comparative Example 1, the commercially available white carbon black wet process rubber SF175-50 in Comparative Example 2, and the white carbon black wet process rubber prepared in Comparative Example 3.
[0065] The raw materials for preparing the mixed rubber of the vulcanized rubber are shown in Table 1 (the fumed silica used in the vulcanized rubber formula of Comparative Example 1 is purchased from Shandong Aochuang Chemical Co., Ltd.). The vulcanization conditions of the vulcanized rubber are: 145°C×30min. The performance test results of the vulcanized rubber prepared by the white carbon black wet process rubber prepared in Examples 1 to 3 and the natural rubber prepared in Comparative Example 1 are shown in Table 2. In Table 2: the ash sample is the white carbon black wet process rubber masterbatch, the optimal vulcanization time sample is the white carbon black wet process rubber mixed rubber, and the test samples of other items are white carbon black wet process rubber vulcanized rubber.
[0066] Table 1 Rubber compound formulas of Examples 1 to 3 and Comparative Examples 1 to 3
[0067] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Example 1 Example 2 Example 3 White carbon black wet process adhesive 0 150 150 150 150 150 Natural rubber 100 0 0 0 0 0 Fumed silica 50 0 0 0 0 0 Zinc Oxide 5 5 5 5 5 5 Stearic acid 1.5 1.5 1.5 1.5 1.5 1.5 Antioxidant 4010NA 1.5 1.5 1.5 1.5 1.5 1.5 Coupling agent KH-845-4 5.0 5.0 5.0 5.0 5.0 5.0 Accelerator CZ 2.0 2.0 2.0 2.0 2.0 2.0 Accelerator D 1.0 1.0 1.0 1.0 1.0 1.0 sulfur 1.5 1.5 1.5 1.5 1.5 1.5
[0068] The specific steps of mixing in an open mill when preparing the vulcanized rubber in Examples 1 to 3 and Comparative Examples 2 to 3 are shown in Table 2:
[0069] Table 2 Specific steps of mixing in an open mill when preparing vulcanized rubber in Examples 1 to 3 and Comparative Examples 2 to 3
[0070]
[0071]
[0072] The method for preparing a compound rubber from the natural rubber prepared in Comparative Example 1 according to the mixed rubber formula in Table 1 specifically includes: first, the natural rubber prepared in Comparative Example 1 is mixed with fumed silica in an internal mixer according to the method in Table 3, and then the mixing is started directly from the mixing step 2 in the open mixer in Table 2.
[0073] Table 3 Comparative Example 1 The steps of mixing the natural rubber with fumed silica in an internal mixer
[0074]
[0075] The performance test results of the vulcanized rubber prepared by the commercially available wet-process white carbon black rubber SF175-50 (manufacturer: Mengla County Manzhuang Rubber Co., Ltd.) of Examples 1 to 3, Comparative Examples 1 and 2 and Comparative Example 3 are shown in Table 4. The white carbon black dispersion is tested using a carbon black dispersion meter.
[0076] Table 4 Test results
[0077]
[0078]
[0079] Among them, the test standards for each test item in Table 4 are shown in Table 5.
[0080] Table 5 Test Standards
[0081] Test items Test Standards Optimum vulcanization time, min GB / T9869-2014 Hardness GB / T531.1-2008 300% tensile stress, MPa GB / T528-2009 Tensile strength, MPa GB / T528-2009 Elongation at break, % GB / T528-2009 Tear strength, kN / m GB / T529-2008 Compression fatigue heat generation, ℃ GB / T1687.3-2014 Ash content, % GB / T4498
[0082] Comparative Example 3
[0083] 10 g of phosphatidylethanolamine was dispersed in water with high-speed stirring to obtain a lecithin emulsion, 500 g of hydrophilic silica (hydrophilic silica was REOLOSIL QS-102 type, purchased from Tokuyama Co., Ltd.) was added to the lecithin emulsion and 1 g of coagulase (papain) was added and stirred thoroughly to obtain a hydrophilic silica emulsion.
[0084] The hydrophilic silica emulsion was blended with natural rubber latex containing 1000 g of dry glue, fully stirred until a viscous paste, transferred to a stainless steel tray and allowed to stand for 12 hours, and dried at 120° C. to obtain a silica wet glue.
[0085] Compared with Example 2, the lecithin in Example 2 is replaced by the surfactant "phosphatidylethanolamine" (Comparative Example 3). After adding phosphatidylethanolamine in Comparative Example 3, the coagulation time of the natural rubber latex becomes longer and the coagulation effect becomes worse (coagulation is incomplete). The reason is that phosphatidylethanolamine is weakly alkaline, which is not conducive to coagulation.
[0086] Example 4
[0087] The preparation method is basically the same as that in Example 2, except that the "hydrophilic silica" used in Example 2 is replaced by "fumed silica", and the specific steps are as follows:
[0088] 10 g of lecithin was dispersed in water with high-speed stirring to obtain a lecithin emulsion, 500 g of fumed silica was added to the lecithin emulsion and 1 g of coagulase (papain) was added and stirred sufficiently to obtain a fumed silica emulsion.
[0089] The fumed silica emulsion was blended with natural rubber latex containing 1000 g of dry glue, fully stirred until a viscous paste, transferred to a stainless steel tray and allowed to stand for 12 hours, and dried at 120°C to obtain a wet silica glue.
[0090] In this embodiment, "fumed silica" is directly mixed with lecithin emulsion. Since the silanol groups on the surface of fumed silica have a certain hydrophilicity, the prepared silica wet-process rubber has good dispersibility, but the silica itself will partially agglomerate, resulting in partial precipitation of the silica wet-process rubber. In contrast, in Example 2, "hydrophilic silica" is used as the raw material for preparation, and the obtained silica wet-process rubber has significantly better dispersibility than the product prepared in Example 4. The hydrophilic silica itself does not agglomerate, and the silica wet-process rubber obtained in Example 2 has no precipitation.
[0091] In Example 1, the precipitation phenomenon of the white carbon black wet process rubber prepared by using "lipophilic white carbon black" as raw material and mixing and emulsifying with phospholipids is improved.
[0092] Comparative Example 4
[0093] 500 g of fumed silica was dispersed in water, and 1 g of coagulase (papain) was added and stirred thoroughly to obtain a fumed silica emulsion.
[0094] The fumed silica emulsion was blended with natural rubber latex containing 1000 g of dry glue, fully stirred until a viscous paste, transferred to a stainless steel tray and allowed to stand for 12 hours, and dried at 120°C to obtain a wet silica glue.
[0095] Comparative Example 4 directly uses "fumed silica" to mix and coagulate with natural rubber latex. After coagulation, a large amount of silica will precipitate, that is, the mixing is uneven. During the processing and mixing process, part of the silica will turn into dust.
[0096] As can be seen from the above embodiments, the present invention provides a method for preparing a white carbon black wet process rubber, comprising the following steps: mixing white carbon black, phospholipid emulsion and coagulase to obtain white carbon black emulsion; mixing the white carbon black emulsion and natural rubber latex to obtain a paste; and sequentially performing static coagulation and drying on the paste to obtain the white carbon black wet process rubber. The preparation method provided by the present invention uses phospholipid as a dispersant and auxiliary coagulase as a coagulant, thereby improving the mechanical properties of the vulcanized rubber, and at the same time, there is no need to pre-emulsify the natural rubber latex, thereby improving the production efficiency of the white carbon black wet process rubber and reducing the cost.
[0097] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a white carbon black wet-process rubber, characterized in that: The following steps are involved: mixing white carbon black, phospholipid emulsion and coagulase to obtain white carbon black emulsion; Mixing the white carbon black emulsion and natural rubber latex to obtain a paste; The paste is sequentially placed to solidify and dried to obtain the white carbon black wet-process glue.
2. The preparation method according to claim 1, characterized in that: The white carbon black includes one or more of fumed white carbon black, hydrophilic white carbon black and oleophilic white carbon black.
3. The preparation method according to claim 2, characterized in that: The preparation method of the oleophilic white carbon black comprises the following steps: A silane coupling agent is used to hydrophobically modify fumed silica to obtain lipophilic silica; the mass percentage of the silane coupling agent in the fumed silica is 10-20%.
4. The preparation method according to claim 1, characterized in that: The phospholipid emulsion comprises phospholipid and water, and the phospholipid comprises one or more of phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass percentage of the phospholipids in the phospholipid emulsion to the white carbon black is 1-5%.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the white carbon black to the dry rubber in the natural rubber latex is 1:2-3.
7. The preparation method according to claim 1, characterized in that: The coagulase is a protease; the mass percentage of the coagulase in the dry rubber in the natural rubber latex is 0.1-1%.
8. The preparation method according to claim 1, characterized in that: The standing solidification time is 8 to 24 hours; the drying temperature is 100 to 120°C.
9. The white carbon black wet-process rubber prepared by the preparation method according to any one of claims 1 to 8.
10. A vulcanized rubber, characterized in that: The preparation comprises the following raw materials in parts by weight: 150-180 parts of the white carbon black wet-process rubber according to claim 9, 3-5 parts of zinc oxide, 1-2 parts of stearic acid, 1-2 parts of antioxidant, 2-6 parts of coupling agent, 2-3 parts of accelerator, and 1-2 parts of sulfur.
Citation Information
Patent Citations
Organosilicon emulsion modified wet-process wear-resistant rubber and preparation method thereof
CN111269470A